A Project Feasibility Study on establishing a brown paper bag manufacturing business Boombag - Dacumos, Marielle Grace D. 4 0 16; 5
u
Feasibility Study: (Bachelor of Science in Accountancy) - Pamantasan ng Lungsod ng Maynila, 2014.
Keywords: 2 -- 0; 6; 20; 20; 2